2020
DOI: 10.3390/app10175768
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Stability of Novel Aqueous Graphene Oxide–Al2O3 Hybrid Nanofluids for Cold Energy Storage

Abstract: Thermal ice storage has gained a lot of interest due to its ability as cold energy storage. However, low thermal conductivity and high supercooling degree have become major issues during thermal cycling. For reducing the cost and making full use of the advantages of the graphene oxide–Al2O3, this study proposes heat transfer enhancement of thermal ice storage using novel hybrid nanofluids of aqueous graphene oxide–Al2O3. Thermal conductivity of aqueous graphene oxide–Al2O3 nanofluid was measured experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Therefore, the hybrid nanofluid can be employed in a wide range of areas, such as electronic cooling, heat exchangers, military equipment, automotive, solar collectors, and refrigeration systems, in place of mono-nanofluids and conventional fluids [1,2]. In addition, hybrid nanofluids can also be used to enhance the heat transfer performance of cold storage and solar thermal energy storage systems (see Shao et al [3]; Dubal et al [4]; Vaka et al [5]; Selimefendigila et al [6]; Gao et al [7]; Maleki et al [8]; and Alrowaili et al [9]). Turcu et al [10], Jana et al [11], and Suresh et al [12] were among the first researchers to do experimental research on the development of hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the hybrid nanofluid can be employed in a wide range of areas, such as electronic cooling, heat exchangers, military equipment, automotive, solar collectors, and refrigeration systems, in place of mono-nanofluids and conventional fluids [1,2]. In addition, hybrid nanofluids can also be used to enhance the heat transfer performance of cold storage and solar thermal energy storage systems (see Shao et al [3]; Dubal et al [4]; Vaka et al [5]; Selimefendigila et al [6]; Gao et al [7]; Maleki et al [8]; and Alrowaili et al [9]). Turcu et al [10], Jana et al [11], and Suresh et al [12] were among the first researchers to do experimental research on the development of hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced thermophysical property of nanofluid caught the attention of many researchers making them study the behavior of different nanoparticles in different based fluids. Yugo Goa et al 5 studied the thermal conductivity of graphene oxide-Al 2 O 3 hybrid nanofluid for a temperature ranging from 0 to 70 C. They reported an increase in thermal conductivity with an increase in temperature and mass fraction of nanoparticles. Suresh et al 6 reported a 12.11% improvement in thermal conductivity for Al 2 O 3 -Cu-Water nanofluid (90:10) for a volume concentration of 2%.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method provides more precise results in less time. In addition, Gao et al [44] investigated the thermal conductivity and stability of graphene oxide-Al 2 O 3 hybrid nanofluid. The result showed that the pH, dispersant, ultrasonication power, and duration affect the stability of the hybrid nanofluid.…”
Section: Introductionmentioning
confidence: 99%